Effect of omega-3 fatty acid oxidation products on the cellular and mitochondrial toxicity of BDE 47. Issue 4 (June 2015) - Yeh, Andrew; Kruse, Shane E.; Marcinek, David J.; Gallagher, Evan P.
Highlights BDE 47 is a toxic PBDE flame retardant and major contaminant in Pacific salmon. Oxidized omega-3 fatty acids (oxEPA/oxDHA) partially prevented BDE 47 toxicity. oxEPA/oxDHA partially protected viability and mitochondrial membrane potential. oxEPA/oxDHA partially protected mitochondrial electron transport system function. Our results indicate oxEPA/oxDHA protects against shorter exposures to BDE 47.